Homerooms & hall passes - O'Donnell, Tom (Balzer + Bray, 2020)
In the fantasy realm of Bríandalör, Thromdurr the barbarian, Devis the thief, Vela the paladin, Sorrowshade the Gloom Elf assassin, and Albiorix the wizard take a break from their hectic adventuring to play the "fantasy" role-playing game Homerooms & Hall Passes in which they are average American eighth graders.